Intakes of caffeine, coffee and tea and risk of Amyotrophic Lateral Sclerosis: Results from five cohort studies - Fondell, Elinor (Amyotroph Lateral Scler Frontotemporal Degener, 2015)
OBJECTIVE: Caffeine is thought to be neuroprotective by antagonizing the adenosine A(2A) receptors in the brain and thereby protecting motor neurons from excitotoxicity. We examined the association between consumption of caffeine, coffee and tea and risk of Amyotrophic Lateral Sclerosis (ALS). METHODS: Longitudinal analyses based on over 1 010 000 men and women in 5 large cohort studies [the Nurses’ Health Study, the Health Professionals Follow-up Study, the Cancer Prevention Study II Nutrition Cohort, the Multiethnic Cohort Study, and the National Institutes of Health – AARP Diet and Health Study]. Cohort-specific multivariable-adjusted risk ratios (RR) and 95% confidence intervals (CI) estimates of ALS incidence or death was estimated by Cox proportional hazards regression and pooled using random-effects models. RESULTS: A total of 1279 cases of ALS were documented during a mean of 18 years of follow-up. Caffeine intake was not associated with ALS risk; the pooled multivariable-adjusted RR comparing the highest to the lowest quintile of intake was 0.96 (95% CI 0.81-1.16). Similarly, neither coffee nor tea was associated with ALS risk. CONCLUSION: The results of this large study do not support associations of caffeine or caffeinated beverages with ALS risk.